Phase separation and structure transition of undercooled Fe75Cu25 melts. (4th May 2018) - Cui, W. C.; Wang, L.; Peng, C. X.; Song, K. K.
ABSTRACT: The rapid quenching processes of Fe75 Cu25 melt at different cooling rate are investigated by molecular dynamics simulation based on embedded atom method. Fe75 Cu25 alloy ribbons are prepared by single roller rapid quenching. Liquid–liquid phase separation (LLPS) happens and the Cu-rich droplets embedded in the Fe-rich matrix can be observed both in simulation and experiments. Stronger interaction of homogeneous atom pairs than that of heterogeneous atom pairs leads to LLPS, controlled by nucleation growth mechanism in Fe75 Cu25 melt, and quite different from that in Fe50 Cu50 melt, which is controlled by spinodal decomposition mechanism. During the crystallisation process after LLPS, the new nuclei form only in Fe-rich regions; various multiply twinning boundaries are formed due to the minimisation of interfacial energy and only the homogeneous atomic stacking shows mirror symmetry along twinning boundary. The results provide atomic-scale understanding of phase separation mechanism and structure transition of Fe75 Cu25 melt during rapid cooling processes.